Predicting mortality among older adults hospitalized for community-acquired pneumonia: An enhanced Confusion, Urea, Respiratory rate and Blood pressure score compared with Pneumonia Severity Index - Abisheganaden, J. (2016)
10.1111/j.1440-1843.2012.02183.x